2020
DOI: 10.1111/bcpt.13534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of single nucleotide polymorphism of LAT1 on therapeutic response to gabapentinoids in Pakistani patients with neuropathic pain

Abstract: Gabapentinoids are substrate of L‐type amino acid transporter 1 (LAT1) for distribution across the blood‐brain barrier. The present study aimed to evaluate the effect of LAT1 rs4240803 genetic polymorphism on the clinical efficacy and tolerability of gabapentinoids in Pakistani patients with neuropathic pain. Three‐hundred and ninety‐two patients were recruited, genotyped for SNP rs4240803, and followed up for eight weeks to evaluate the clinical response to gabapentinoids in terms of pain relief, inadequate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Genotyping of the relevant polymorphisms may predict the response of the drug and decrease the duration for dose titration thereby reducing the probability of adverse events during dose adjustments. [12][13][14] A genetic polymorphism modifying the structure of the proteins that metabolize drugs may significantly change the pharmacokinetic properties of calcineurin inhibitors eventually causing fluctuations in the time required for dose titration to attain optimum drug levels in the blood. 15 Polymorphism in CYP3A4 and the interrelated PPARA gene have a crucial role in modifying the clinical response of tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of the relevant polymorphisms may predict the response of the drug and decrease the duration for dose titration thereby reducing the probability of adverse events during dose adjustments. [12][13][14] A genetic polymorphism modifying the structure of the proteins that metabolize drugs may significantly change the pharmacokinetic properties of calcineurin inhibitors eventually causing fluctuations in the time required for dose titration to attain optimum drug levels in the blood. 15 Polymorphism in CYP3A4 and the interrelated PPARA gene have a crucial role in modifying the clinical response of tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
“…The role of L-type amino acid transporter (LAT1) polymorphism has been suggested in the absorption and distribution of gabapentinoids [26]. Our recent study has reported the significant association of LAT1 rs4240803 variant genotype in the variable clinical efficacy and poor tolerability in Pakistani patients with neuropathic pain [27]. To the best of our knowledge, the present study is the first to report the possible association of OCTN1 L503F and rs3792876 on OCTN1 substrates, gabapentin and pregabalin in the South Asian population.…”
Section: Plos Onementioning
confidence: 99%